Audit incidents for selected local authorities in Malaysia / Asmah Haji Abdul Aziz and Emilin Abdul Wahid - Abdul Aziz, Asmah; Abdul Wahid, Emilin (2004)
This study examines the audit certificates and financial statements of selected local authorities. The main aspects emphasized in the study are the types of report issued and audit incidents exist in the certificates. 51 of the selected local authorities were analysed for eleven years from year 1990 to 2000, i.e. 561 audited financial statements. Audit reports were classified into three types, that is Clean Report (CR), Audit Qualification (AQ) and Comment Short of Audit Qualification (CSAQ). Based on the reports issued, most of the financial reports of local authorities did not achieve the expected standards. The types of report issued were 169 CR, 8 AQ and 384 CSAQ. Pertaining to the audit incidents there is variability in the pattern of the incidents. Some of the councils have many while some have very few incidents and some are free from any errors. This may suggests that it is not impossible to totally eliminate audit incidents and get a clean report. Possible explanations for the present of numerous audit incidents are lack of accounting skills and insufficient qualified staffs in preparing the accounts. While incidents occurs under the 'Others' category illustrates the lack of commitment and seriousness in discharging responsibilities. The numerous audit qualifications and audit comments provide evidence that the accounts were frequently violated and this is contrary to the government's expectation. Thus many local authorities should improve the quality of financial reporting and accountability to the public.